Ritchie and Tal Lovejoy - Ed Ricketts:::Creator::::::::::::
Tal (Natalya) Lovejoy holding a blanket or baby, Ritch squatting next to her on the left. Shoes and a bottle of wine on the door step. 'Original' in safe (in folder with photo numbers. 600-607)